Meso and microhabitat analysis and feeding habits of small nektonic characins (Teleostei: Characiformes) in Neotropical streams - Ceneviva-Bastos, Mônica [UNESP]; Casatti, Lilian [UNESP]; Rossa-Feres, Denise Cerqueira [UNESP] (Sociedade Brasileira de Zoologia, 2010)
The habitat use and feeding habits of a set of nektonic fish species often found in small low-gradient streams in Brazil were investigated. The core species in the present study was Knodus moenkhausii (Eigenmann & Kennedy, 1903), the most abundant of five species in the nektonic guild. Records of the species in 22 streams indicate that K. moenkhausii is associated, on a mesohabitat scale, with runs, and on a microhabitat scale, with sandy bottoms, intermediate depth, and open sites without coverage or submerged vegetation. During snorkeling observations, two additional nektonic registered species showed spatial segregation from K. moenkhausii with respect to foraging microhabitats. Feeding habits of the observed nektonic species were significantly correlated with riparian vegetation. The six species studied appear to use different resources, as suggested by a non-metric ordination of diet, and sites with characteristic riparian vegetation. The studied species may be considered generalists with a tendency to insectivory, with K. moenkhausii feeding on the widest variety of resources. Such opportunism explains its ability to successfully occupy instream habitats with low complexity.
Keywords: Characidae; habitat use; resources; Upper Paraná